THE ROLE OF MOBILE APPLICATIONS IN TEACHING ENGLISH VOCABULARY TO 9TH GRADE STUDENTS: A THEORETICAL REVIEW WITH PRACTICAL INSIGHTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This theoretical article examines the pedagogical, psycholinguistic, and linguistic underpinnings of using mobile applications to teach English vocabulary to 9th-grade students. With the advent of mobile learning (m-learning), vocabulary acquisition can now occur in more autonomous, engaging, and personalized ways. Drawing from scholarly perspectives and personal observations as an English teacher and researcher, the article evaluates both the promise and the pitfalls of using mobile apps such as Quizlet, WordUp, and Duolingo in classroom and self-study contexts. Through an interdisciplinary lens, it offers a critical exploration of how vocabulary learning is influenced by technology and provides recommendations for maximizing mobile learning’s potential.